A deficiência visual e o mundo microscópico: modelos didáticos - uma metodologia alternativa - Michelotti, Angela (2018)
The use of didactic models in Science teaching becomes a didactic alternative to integrate students with Visual Deficiency into regular classes. With the use of cell didactic models we are able to bring the microscopic world for Seers and non-Seers students. The objective of this research was to test the hypothesis if alternative methodological activities, through the use of Didactic Models, can help Seers and Visual Deficits students in learning basic Cytology concepts. The total number of participants was: 23 seers students and 5 students with visual impairment (3 blind, and 2 with low vision), of 8th and 9th grade, elementary school. The research took place in 5 moments: a) pretest, b) tactile perception activity, c) researcher intervention, d) posttest I and e) posttest II - interview after 5 months. The results are presented in two manuscripts. In the first manuscript, attend to he question about the coexistence in the classroom, of seers and non-seerns colleagues, seers and Visual Impairments and about the teaching and learning of Sciences. It was noticeable that inclusion benefits both the student with Visual Impairments and the student without Disabilities in the matter of their personal growth, and in the interaction with their colleagues. It is in the school environment that students are faced with diversity, they realize that each has its individuality and uniqueness. The second manuscript address the use of didactic models as alternative methodologies for the teaching of the following cytology concepts: cellular forms, cellular multiplication process and skin cicatrization. The results showed that the students obtained a greater understanding with the use of the presented methodology, being able to be perceived in their answers greater clarity and objectivity, after the accomplishment of the activities. The use of three-dimensional models designed to be felt and visualized, contributes to the inclusion of the Visually Impaired student, together with the sighted student. The sighted students were able to use another meaning, in addition to the vision to first "see" the cells, experiencing some of the difficulties encountered by their colleagues.